2020
DOI: 10.3390/foods9030290
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Processing and Intestinal Conditions on in Vitro Digestion of Chia (Salvia hispanica) Seeds and Derivatives

Abstract: Chia seeds present with an excellent nutrient profile, including polyunsaturated fat, protein, fibre and bioactive compounds, which make them a potential food or ingredient to bring beneficial health effects. However, their tough structure could mean that these seeds remain hardly disrupted during digestion, thus preventing the release and digestibility of nutrients. In the present study, different chia products (seeds, whole flour, partially defatted flour and sprouts) were assessed in terms of proteolysis, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…Some of the components that the fungus takes as substrates are present in the plant cell walls 25 , so its degradation could facilitate eventual structural breakdown in the milling process as compared to unfermented substrates. The reduction of the particle size of a food substrate has been repeatedly associated with increased digestibility and bioaccessibility of nutrients in nuts and seeds 28,29 . This observation is explained by the fact that the higher the matrix disruption, the easier the nutrients release to the digestion medium, leading to higher enzyme-substrate accessibility.…”
Section: Impact Of Fermentation On Physical Characteristics and Nutrient Profilementioning
confidence: 99%
“…Some of the components that the fungus takes as substrates are present in the plant cell walls 25 , so its degradation could facilitate eventual structural breakdown in the milling process as compared to unfermented substrates. The reduction of the particle size of a food substrate has been repeatedly associated with increased digestibility and bioaccessibility of nutrients in nuts and seeds 28,29 . This observation is explained by the fact that the higher the matrix disruption, the easier the nutrients release to the digestion medium, leading to higher enzyme-substrate accessibility.…”
Section: Impact Of Fermentation On Physical Characteristics and Nutrient Profilementioning
confidence: 99%
“…Roasting and popping leads to decrease in the calcium content of the chia seeds. Calvo-Lerma et al, (2020) also reported that germination promotes the hydrolysis of chia proteins, making them completely digestible, and causes a significant increase in polyphenols and calcium concentration in chia sprouts. Phosphorus content was significantly increased (3.57%) during germination, while it decreased significantly during roasting and popping.…”
Section: Chia Seedsmentioning
confidence: 95%
“…Animal models have been extensively applied to assess the digestion process, but the fact that animals' microbiota differ from humans' microbiota is widely accepted [6]. For these reasons, alternative methodologies to study digestion have increased, including in vitro digestion models, which enable the simulation of digestion in the laboratory [7][8][9][10]. These models allow for the possibility of sampling at any point of the process, assessing digestion of any food or nutrient and establishing its effect on the microbiota profile, or determining the products generated by the microbiota metabolism [7,11].…”
Section: Introductionmentioning
confidence: 99%